Knowledge, Acceptance And Perception On COVID-19 Vaccine Among Malaysians: A Web-based Survey - Nurul Azmawati Mohamed @ Abd Aziz; Hana Maizuliana Binti Solehan; Mohd Dzulkhairi Bin Mohd Rani; Muslimah Ithnin; Che Ilina Binti Che Isahak (The Public Library of Science (PLOS), 2024)
Indexed by WOS/SCOPUS/ERA